Transvaginal artificial ascites infusion as a spacer in gynecological brachytherapy: a novel technique - Karube, Masataka; Murakami, Naoya; Okamoto, Hiroyuki; Okuma, Kae; Kashihara, Tairo; Takahashi, Kana; Kaneda, Tomoya; Inaba, Koji; Igaki, Hiroshi; Kato, Tomoyasu; Itami, Jun (Journal of Contemporary Brachytherapy, 2020)
This is a first paper to report on artificial ascites infusion via vaginal wall for pelvic interstitial brachytherapy. Artificial ascites is commonly used for treating liver tumors, with radiofrequency ablation and percutaneous artificial ascites infusion through the abdominal wall for pelvic brachytherapy has been previously reported by our group. However, the trans-abdominal needle approach under ultrasound guidance is unreliable due to poor visualization resulting in fluid injection into the abdominal wall or mesenterium and the rate of successful artificial ascites infusion was low. Target tumor of the vaginal cuff brachytherapy is usually adjacent to the intestine, and transvaginal artificial ascites infusion under trans-rectal ultrasonography is considered as a rational and simpler method to create a space between target volume and organs at risk, such as intestines or sigmoid colon, by increased visualization of the needle compared to trans-abdominal approach. Here, we report a practical experience of transvaginal artificial ascites infusion